Gambaran Gambaran pengetahuan pasien TB paru tentang pentingnya pengobatan tuntas diwilayah kerja Puskesmas Cibiru: Pentingnya Pengobatan Tuntas pada Psien TB - Darajat, Agus Miraj; Yosinta, Yossy; Anri, Anri; Muslim, Dede Nur Aziz; Pratama, Angga satria (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2022)
Background: Tuberculosis is a major health problem in the world. The number of tuberculosis cases in 2020 has reached 845,000 confirmed cases worldwide and 98,000 deaths due to tuberculosis. From June to December 2021, data for patients with confirmed pulmonary TB in the working area of the Cibiru Health Center reached 256 cases, and was the area with the highest positive cases reaching 32 cases with patients confirmed positive for pulmonary TB. Purpose: To describe the knowledge of pulmonary TB patients about the importance of complete treatment in the working area of the Cibiru Health Center. Method: This type of research uses total sampling with the number of samples used are 32 people from the total population. Data collection used a questionnaire which totaled 18 questions offline using paper which was distributed to each pulmonary TB patient. Results: Knowledge of the importance of complete treatment in the sense that most (56.3 percent) have less understanding. Knowledge The importance of complete treatment in treatment goals most (59.4 percent) have less treatment goals. Knowledge The importance of complete treatment in the principle of treatment half of the respondents (59.4 percent) had the principle of sufficient treatment. Knowledge The importance of complete treatment in treatment outcomes almost half (34.4 percent) had good treatment outcomes. Knowledge The importance of complete treatment in treatment failure almost half (59.4 percent) had less treatment failure. Conclusion: Most of the respondents had sufficient knowledge of pulmonary TB patients. Suggestion: It is hoped that the Cibiru Health Center can provide support to the community in providing health education as a means and infrastructure to add insight into the importance of complete treatment of pulmonary TB. Pendahuluan: Tuberkulosis merupakan masalah kesehatan yang besar di dunia. Jumlah kasus tuberculosis pada tahun 2020 mencapai 845.000 kasus terkonfirmasi diseluruh dunia dan 98.000 kasus kematian karena tuberculosis. Sejak Juni hingga Desember 2021 data pasien terkonfirmasi TB Paru diwilayah kerja Puskesmas Cibiru mencapai 256 kasus, dan merupakan wilayah dengan kasus positif tertinggi mencapai 32 kasus dengan pasien terkonfirmasi positif TB Paru. Tujuan: Untuk mengetahui gambaran pengetahuan pasien TB Paru tentang pentingnya pengobatan tuntas diwilayah kerja Puskesmas Cibiru. Metode: Jenis penelitian ini menggunakan total sampling dengan jumlah sampel yang digunakan adalah 32 orang dari total populasi. Pengumpulan data menggunakan kuesioner yang berjumlah 18 pertanyaan secara offline menggunakan kertas yang disebar ke setiap pasien TB Paru. Hasil: Pengetahuan Pentingnya pengobatan tuntas dalam pengertian sebagian besar (56,3 persen) memiliki pengertian kurang. Pengetahuan Pentingnya pengobatan tuntas dalam tujuan pengobatan sebagian besar (59,4 persen) memiliki tujuan pengobatan kurang. Pengetahuan Pentingnya pengobatan tuntas dalam prinsip pengobatan setengah rsponden (59,4 persen) memiliki prinsip pengobatan cukup. Pengetahuan Pentingnya pengobatan tuntas dalam hasil pengobatan hampir setengah (34,4 persen) memiliki hasil pengobatan baik. Pengetahuan Pentingnya pengobatan tuntas dalam kegagalan pengobatan hampir setengahnya (59,4 persen) memiliki kegagalan pengobatan kurang. Simpulan: Sebagian besar responden sudah cukup dalam pengetahuan pasien TB Paru. Saran: Diharapkan bagi Puskesmas Cibiru dapat memberikan dukungan kepada masyarakat dalam menyediakan penyuluhan kesehatan sebagai sarana dan prasarana dalam menambah wawasan dalam pentingnya pengobatan tuntas TB Paru.